Livestock producers' knowledge, attitude, and behavior (KAB) regarding antimicrobial use in Ethiopia - Takele B. Tufa; Takele B. Tufa; Fikru Regassa; Kebede Amenu; Kebede Amenu; J. A. Stegeman; Henk Hogeveen; Henk Hogeveen (Frontiers in Veterinary Science, 2023)
IntroductionInappropriate antimicrobial use (AMU) in livestock production is an important aspect of the global burden of antimicrobial resistance (AMR). In Ethiopia, a low-income country with a large and increasing livestock population, AMU in food animals is not properly regulated. Hence, farmers are fully free to use antimicrobials to their (perceived) benefit. Therefore, understanding farmers' mindsets is important to improve antimicrobial stewardship in the livestock sector.MethodsThis cross-sectional study was conducted to assess livestock disease management practices and knowledge, attitude, and behavior (KAB) among livestock producers regarding AMU, residues, and resistance, as well as factors potentially explaining differences in KAB. We determined the KAB of livestock owners of three selected districts of central and western Ethiopia (n = 457), using a pretested questionnaire administered through face-to-face interviews. Logistic regression was used to evaluate the association between potential explanatory variables and the KAB scores of the respondents.ResultsThe results showed that 44% of the farmers used antimicrobials in the past few years, where antibiotics (21%) and trypanocides (11%) were most widely used to manage livestock diseases. Furthermore, most farmers showed poor knowledge about AMU, residues, and AMR (94%) and unfavorable attitudes (<50% correct answers) toward contributing factors for AMR (97%). On the contrary, 80% of the respondents had overall good behavior scores (≥50% correct answers) related to AMU. Multivariate analysis results showed that having good knowledge, keeping ≥2 animal species, and the occurrence of ≥4 livestock diseases on the farm in a year were strong predictors of bad behavior scores (p < 0.05). The findings of the current investigation also revealed that the incidence of livestock diseases on the farm and a higher level of formal education significantly contributed to better knowledge and desirable attitudes but bad AMU behavior.ConclusionA low level of awareness about and undesirable attitudes toward AMU and AMR could potentially affect farmers' behavior toward judicious AMU, thus requiring awareness creation efforts on livestock disease management practices.